Gross Motor Skills in Early Grade Students: A Bibliometric Study - Rojas, Yesica Rosario Felices-; Teves, Selene del Carmen Alcantara-; Revatta, Andrea Angelica Donayre-; Chacaltana, María del Carmen Ayala-; Arones, Herlinda Liliana Vásquez-; Mejia, Nathaly Rosmery Gomez- (International Journal of Membrane Science and Technology, 2023)
Gross motor skills refer to fundamental motor skills such as running, walking, crawling, jumping and catching. This domain requires adequate coordination of muscular, skeletal and nervous system activity. The objective was to perform a bibliometric analysis of the literature indexed in Scopus on gross motor skills in students of the initial level, between 2003 and 2023. Methodologically, it was a quantitative bibliometric study. The scientific production indicators were generated from 498 documents selected from Scopus using keywords in English ("gossip", "motor", "skills", "childhood"). From 2016 to 2022, published papers increased (66.1%), indicating a growing interest in the subject of study. The United States is the country with the most scientific production (21.3%; n=157), and the University of Wollongong in Australia, has the most publications (n=21). The International Journal of Environmental Research and Public Health published 24 papers, while the most cited was Developmental Medicine and Child Neurology with 707 citations, with author Goodway, J.D. (n=10 papers) being the most cited (n=682). From the studies analyzed, it is concluded that the early stages of a child’s life are vital for the growth of gross motor skills, which in turn fosters the acquisition of knowledge, independence and confidence. Consequently, early learners can benefit from physical activity, as it helps them refine their motor skills by giving them the opportunity to work on balance, control and coordination.